Determinação do limiar anaeróbio por meio de dosagens glicêmicas e lactacidêmicas em testes de pista para corredores (Revista Paulista de Educação Física, 1998)
In order to compare the Anaerobic Threshold (AT) determined by blood lactate (lac) and to verify the possibility of AT determination by blood glucose (gluc) measurements, 12 male endurance runners (aged 25.5 + 7.0) performed four running track tests: a) 3.000 m performance (Vm3Km); b) equilibrium point between lac production and removal (Lacmin): 1 x maximal 500 m followed by 6 x 800 m progressive bouts (87 to 98% of Vm3Km) with 45 sec rest. The velocity (vel) associated with lower [lac] was considered as AT; c) individual anaerobic threshold (IAT): 8 x 800 m progressive bouts (84 to 102% of Vm3Km), with 45 sec rest. The AT vel was determined considering lac kinetic during the test and recovery; d) AT of [4 mM] lac (Vel4mM): Interpolation between lac and vel in 2 x 1200 m at 85 and 100% of Vm3Km, with 10 minutes rest; e) the vel associated at lower glue during IAT ( 0.05; see table below). IAT Lacmin Vel4mM